Emodiluizione Intenzionale Isovolemica e Risparmio di Sangue in Chirurgia - G. Martinelli; A. Zanoni; E. Aldrovandi; P. Bonoli; B. Borghi; S. Faenza; L. Ortelli (AboutScience Srl, 1991)
Abstract non disponibile